Analisis Employee Engagement Pada PT Xyz: Investigasi Peran Flexible Working Arrangement, Perceived Organizational Support, Work-Life Balance, dan Job Satisfaction - Eka Junis Setyawan; Stefanus MS Sadana (Riviera Publishing, 2025)
This study aims to investigate the role of flexible working arrangement, perceived organizational support, work-life balance, and job satisfaction in increasing employee engagement in switching service provider companies. The research method used the Variance-based SEM approach with the Partial Least Squares (PLS) technique through SmartPLS software, and sample determination using the Slovin method. The results showed that flexible working arrangement, perceived organizational support, and job satisfaction had a positive and significant effect on employee engagement, while work-life balance had no direct effect. However, job satisfaction has been proven to mediate the relationship between the three independent variables (flexible working arrangement, perceived organizational support, and work-life balance) and employee engagement. These findings indicate that although work-life balance does not have a direct effect, it plays an important role through increasing job satisfaction first. The implications of this study provide insight for switching service provider companies in developing effective human resource management strategies, with an emphasis on increasing job satisfaction as a key factor in building optimal employee engagement.